Antibacterial moisture-removing composite material, preparation method thereof and application of antibacterial moisture-removing composite material to sports shoes

By using antibacterial and moisture-exhaust composite materials with silver ion composites, copper-zinc alloy composites and other components in sports shoes, the problems of unstable antibacterial properties and insufficient moisture-exhaustness in existing sports shoes are solved, and higher comfort and hygiene performance are achieved.

CN119798832APending Publication Date: 2025-04-11GUANGZHOU STEPPE FOOTWEAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510097712.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing sports shoes have instability and difficulty in both antibacterial and moisture removal, resulting in moisture accumulation and bacterial growth.

Method used

An antibacterial moisture-exhaust composite material is used, which consists of silver ion composite, copper-zinc alloy composite, graphene, bamboo fiber, polyurethane foam and EVA material, and is prepared by a hot pressing process.

Benefits of technology

It achieves long-term and long-lasting antibacterial and moisture-exhaustible properties, significantly improves the comfort and hygiene performance of sports shoes, and solves the problems of moisture accumulation and bacterial growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798832A_ABST
    Figure CN119798832A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sneaker manufacturing, and discloses an antibacterial moisture-removing composite material, which comprises the following components by weight: 50-70 parts of a silver ion compound; the invention also provides a preparation method of the antibacterial moisture-removing composite material, and the method comprises the following steps: S1, preparing the antibacterial component: mixing a silver ion solution with copper-zinc alloy powder in proportion, and reacting at the temperature of 100-150 DEG C for 2-4 hours to form a silver ion and copper-zinc alloy compound, so as to obtain the antibacterial moisture-removing composite material; the invention also provides an application method of the antibacterial moisture-removing composite material on sports shoes. The antibacterial moisture-removing composite material comprises a sole part, a vamp part and an insole part. According to the antibacterial and moisture-removing composite material, the graphene, the silver ion compound, the bamboo fibers and the tea tree oil are combined, so that the antibacterial property and moisture-removing property of the sports shoes are improved, and the comfort and sanitation after long-time use are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sports shoe manufacturing, in particular to an antibacterial moisture-wicking composite material and a preparation method and application thereof in sports shoes. Background Art

[0002] As people exercise more, the functional requirements for sports shoes are gradually diversified. In addition to basic comfort, shock absorption and wear resistance, more and more consumers are beginning to pay attention to the antibacterial and moisture-wicking properties of sports shoes. Especially after long-term exercise, sweat accumulation, bacterial growth and odor on the feet not only affect the wearing experience, but may also cause foot health problems. In order to meet these needs, traditional footwear products use different materials and technical means to improve the functionality of sports shoes.

[0003] In the prior art, many sports shoes use materials such as silver ion coatings and bamboo charcoal fibers to improve the antibacterial properties of the uppers. These technologies can effectively inhibit the growth of bacteria and reduce the generation of odor. However, most of these methods have the problem of unstable antibacterial effects and are easily weakened by factors such as friction and sweat. For example, the silver ion coating may fall off after long-term use, and the antibacterial properties of bamboo charcoal fibers will also decrease with friction loss. In addition, although traditional upper materials have improved air permeability, they do not effectively combine antibacterial and moisture removal functions, resulting in moisture accumulation in the shoes, affecting the wearer's comfort.

[0004] However, the antibacterial and moisture-wicking properties in the prior art are often not taken into account at the same time. The soles and insoles of many sports shoes are made of materials with good air permeability, such as porous foam and breathable fibers. These materials can effectively promote the discharge of moisture, but at the same time, these materials usually lack lasting antibacterial functions, resulting in the accumulation of moisture and the breeding of bacteria after long-term wear. In addition, although many insoles and sole materials on the market have good moisture-wicking effects, they lack effective antibacterial treatment, resulting in humid air in the shoes, and bacteria can still breed in warm and humid environments. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides an antibacterial and moisture-wicking composite material, a preparation method and an application in sports shoes, which solve the problems of the prior art in which the antibacterial property is not durable and the moisture-wicking property is insufficient.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: an antibacterial and moisture-wicking composite material, the composite material comprising the following components in parts by weight: Silver ion complex: 50-70 parts; Silver ions have strong antibacterial properties. They combine with bacterial cell walls to destroy the structure of the cell walls, further inhibiting the growth of bacteria or causing their death. Silver ions can also interfere with the enzyme activity in bacteria and inhibit their metabolism. In addition, silver ions can combine with bacterial DNA to hinder their replication and reproduction process, thereby effectively avoiding the spread of bacteria. Copper-zinc alloy composite: 30-50 parts; Both copper and zinc ions have antibacterial effects. Copper ions can destroy the structure of cells by interacting with bacterial cell walls and cell membranes, thereby preventing bacterial growth and reproduction; while zinc ions can interfere with bacterial protein synthesis and RNA synthesis, inhibiting bacterial metabolism. The combination of copper-zinc alloy complexes in the material not only enhances the antibacterial effect, but also avoids the drug resistance problem that may be caused by a single metal ion, providing a wider antibacterial spectrum. Graphene: 3-6 parts; The two-dimensional structure of graphene gives it a large specific surface area and very high thermal conductivity. In composite materials, the addition of graphene improves the thermal conductivity of the material, allowing the soles, insoles and other parts to quickly dissipate heat during exercise and avoid moisture accumulation. The hydrophilicity of graphene itself also enhances its ability to adsorb and diffuse moisture, helping to accelerate the discharge of water vapor. Bamboo fiber: 10-20 parts; Bamboo fiber has good hydrophilicity and hygroscopicity, can quickly absorb sweat produced by the feet, and diffuse moisture to other areas of the composite material through its natural fiber structure to avoid local moisture. The natural components in bamboo fiber (such as bamboo phenol and bamboo acid) have certain antibacterial effects and can inhibit the growth of bacteria. This natural antibacterial property works synergistically with the silver ions and copper-zinc alloy in the composite material to further enhance the antibacterial properties of the composite material. Polyurethane foam: 5-10 parts; Polyurethane foam has excellent elasticity and cushioning properties, which can effectively disperse the pressure of the foot during exercise, reduce friction and discomfort. In addition, the pore structure of PU foam helps to improve the air permeability and moisture discharge of the composite material, further promoting the discharge of moisture and avoiding moisture accumulation; EVA material: 50-70 parts; The main function of EVA material is to provide support and comfort for sports shoes. Its low density and high elasticity enable the soles, insoles and other parts to effectively absorb impact and reduce the pressure on the feet during exercise. At the same time, it works synergistically with other components in the composite material (such as silver ions, bamboo fiber, graphene, etc.). EVA material not only maintains the comfort of the shoes, but also helps to diffuse and discharge moisture through its microporous structure. Tea tree oil: 0.5-2 parts; Tea tree oil interacts with bacterial cell membranes, destroys the integrity of the cell membrane, and inhibits bacterial growth and reproduction. The volatile components of tea tree oil can be released in the shoe, continuously providing antibacterial protection and effectively preventing the growth of bacteria and fungi. Due to the natural source of tea tree oil, its use in composite materials does not affect the comfort of the shoe and can maintain its natural antibacterial effect.

[0007] The present invention provides a method for preparing an antibacterial and moisture-wicking composite material, the method comprising the following steps: S1, preparing an antibacterial component, mixing a silver ion solution and a copper-zinc alloy powder in proportion, reacting at a temperature of 100 to 150° C. for 2 to 4 hours to form a composite of silver ions and the copper-zinc alloy; S2, preparing a dehumidification component, mixing the graphene powder with a solvent by ultrasonic dispersion to ensure uniform distribution of the graphene; S3, preparing bamboo fiber, first pre-treating to remove impurities, then soaking the bamboo fiber in a tea tree oil solution with a soaking concentration of 5-10%, and drying the soaked bamboo fiber; S4, preparing polyurethane foam by chemical foaming method, the foaming temperature is controlled at 60-80° C., the foaming time is 10-20 minutes, and the amount of foaming agent added is 2-5% of the total weight of the polyurethane foam; S5. Mix the antibacterial component, the moisture-removing component and the EVA material, and obtain an antibacterial and moisture-removing composite material by a hot pressing molding method with the temperature controlled between 120 and 150° C. and the molding time being 10 to 30 minutes.

[0008] Preferably, the preparation method of the silver ion complex and the copper-zinc alloy complex is: The silver ion solution and the copper-zinc alloy powder are mixed in a weight ratio of 50 to 80 parts of silver ions to 20 to 50 parts of copper-zinc alloy, the reaction temperature is controlled between 100 and 150° C., and the reaction time is 2 to 4 hours; The composite of copper-zinc alloy can not only improve the antibacterial efficacy, but also avoid the problem of diminishing antibacterial effect of a single component. The composite reaction of silver ions and copper-zinc alloy at this temperature can effectively improve the stability and antibacterial effect of the composite. High temperature accelerates the composite reaction, allowing silver ions to be stably embedded in the lattice structure of the copper-zinc alloy. The silver ion solution is a water-soluble silver salt solution, and the particle size of the copper-zinc alloy powder ranges from 1 to 5 microns; Silver ions are reduced to silver (Ag). The reduction process uses a reducing agent such as sodium hydride or glucose to provide electrons to reduce the silver ions. The addition of the reducing agent promotes the reduction process of the silver ions, allowing them to be stably embedded in the lattice structure of the copper-zinc alloy. This particle size range can ensure the high efficiency of the reaction, while increasing the contact area between the silver ions and the copper-zinc alloy, which is conducive to the composite reaction. The mixing reaction is carried out under a constant temperature condition, and an appropriate amount of reducing agent can be added during the mixing process to promote the composite reaction of silver ions and copper-zinc alloy; The combination of silver ions and copper-zinc alloy not only improves the antibacterial efficacy of silver, but also enhances the antibacterial effect of copper-zinc alloy. Silver ions can interact with bacterial cell membranes, destroy cell walls, and inhibit bacterial growth, while copper-zinc alloys further destroy the bacterial biofilm structure by producing reactive oxygen species (ROS).

[0009] Preferably, the graphene dispersion method comprises: Mixing graphene powder with solvent and evenly dispersing it through an ultrasonic dispersing device to ensure uniform distribution of graphene and avoid agglomeration; The use of ultrasonic dispersion technology in the solvent helps to effectively disperse graphene, avoid agglomeration, and ensure its uniform distribution in the solution. After dispersion, graphene can form a stable network structure in the composite material, enhancing the overall performance of the material. At the same time, through the high thermal conductivity of graphene, it can effectively accelerate the release of heat in the soles, insoles and other parts, thereby promoting the discharge of moisture; The solvent is water, ethanol or ethylene glycol, the power of the ultrasonic dispersion device is 200 to 500 W, and the ultrasonic treatment time is 30 to 60 minutes; According to the power (200-500W) and processing time (30-60 minutes) of the ultrasonic dispersion device, the ultrasonic energy can continuously act on the graphene particles, increase the collision between the particles, and promote their uniform distribution in the solvent. Higher power and time can provide more energy to thoroughly disperse the graphene particles, while longer time can further optimize the dispersion effect; during the dispersion process, dispersants are added to ensure the stable dispersion of graphene and prevent it from agglomerating; During the dispersion process, adding dispersants (such as surfactants, polyvinyl pyrrolidone, etc.) can effectively reduce the cohesion between particles. The dispersants physically adsorb to the graphene surface through their molecular chains to form a thin film to prevent the graphene particles from aggregating again.

[0010] Preferably, the pretreatment step of the bamboo fiber comprises: After the bamboo fiber is physically treated to remove surface impurities, it is then chemically treated to remove oil and natural resin. After the treatment, tiny pores are formed on the surface of the bamboo fiber, which improves its ability to bind tea tree oil. During the pretreatment process, physical methods are first used to remove impurities on the surface of bamboo fibers. These impurities may be dust, impurities in the external environment, or some larger particles originally attached to the surface of bamboo fibers. Then, chemical treatment is used to remove these oils and resins, exposing the surface active groups of bamboo fibers, increasing their hydrophilicity and affinity with external solutions. After physical and chemical treatment, tiny pores will form on the surface of bamboo fibers. These tiny pores help to improve the hygroscopicity of bamboo fibers and enhance their ability to bind with tea tree oil, thereby further enhancing the moisture removal and antibacterial properties of bamboo fibers in composite materials. Physical treatment methods include steam treatment or mechanical stretching, and chemical treatment includes acid and alkali treatment; The concentration of the tea tree oil solution is 5-10%, and the soaking time is 2-4 hours. After that, the bamboo fiber is naturally air-dried or dried to remove excess solvent and maintain the natural properties of the bamboo fiber. The terpenes in tea tree oil (such as tea tree alcohol) have strong antibacterial, antifungal and antiviral effects. During the soaking process, tea tree oil is absorbed into the bamboo fiber through the tiny pores on the surface of the bamboo fiber. The microporous structure of bamboo fiber provides more surface area, allowing tea tree oil to evenly penetrate and combine with the molecular structure of bamboo fiber, thus giving bamboo fiber antibacterial properties; and through natural air drying or drying, bamboo fiber removes excess tea tree oil solution and solvent, ensuring the uniform distribution of tea tree oil in bamboo fiber and preventing excessive solvent residue from affecting the final performance of the material. Air drying or drying helps bamboo fiber maintain its natural structure and properties, while preventing the volatilization of solvents from damaging the environment and the bamboo fiber itself.

[0011] Preferably, the foaming process of the polyurethane foam includes: The foam is prepared by chemical foaming method, the foaming temperature is controlled between 60 and 80°C, the foaming time is 10 to 20 minutes, and the amount of foaming agent added is 2 to 5% of the total weight of the polyurethane foam; This temperature range can provide an appropriate reaction rate, so that the foaming agent releases gas uniformly, while avoiding the adverse effects of too low or too high temperature; this temperature range can smoothly control the foaming reaction rate to ensure that the structure of the foam is stable and uniform; the time setting of 10 to 20 minutes can ensure that the foam is fully expanded and the pore structure is stable. This time range can effectively ensure the uniform expansion of the foam, ensure the release of gas and the stability of the material, and avoid the problem of foam expansion too early or too late. At the same time, too low an amount of foaming agent may lead to insufficient gas release and insufficient foam expansion, resulting in excessively high foam density and lack of buffering performance. If the amount added is too high, too much gas may cause the foam to expand too quickly and form an unstable structure. Therefore, selecting a foaming agent addition amount of 2 to 5% can maintain the stability and uniformity of the foam while ensuring sufficient foam volume; the chemical foaming agent is hydrated dichloromethane or an alkyl sulfonate compound, and the volume expansion coefficient of the foam is 3 to 5 times; hydrated dichloromethane or an alkyl sulfonate compound will decompose when heated to release gas, such as carbon dioxide or nitrogen. These gases expand in the polyurethane matrix to form a foam structure. By adding 2-5% of the foam, it is possible to ensure that the foam is fully expanded while avoiding excessive expansion or uneven foam caused by too much foaming agent. Too much foaming agent will release too much gas, resulting in unstable foam, while too little foaming agent cannot provide enough gas to generate foam, affecting the volume and elasticity of the foam. During the foaming process, the foaming agent is mixed evenly with the polyurethane and then heated to react. The temperature change during the foaming process is controlled between 70 and 85°C to ensure that the foam structure is uniform and stable. This temperature range can avoid excessive expansion of the foam, ensure a stable rate of gas release, make the foam structure more uniform, and have appropriate elasticity. Slow heating within this temperature range can ensure uniform expansion of the polyurethane material while ensuring the stability of the foam pores.

[0012] Preferably, the mixing method of the EVA material comprises: The antibacterial component, the moisture removal component and the EVA material are mixed in a ratio of 50 to 70 parts, and hot-pressed to form the mixture. The forming temperature is controlled between 120 and 150° C., and the forming time is 10 to 30 minutes. In the composite material, the proportion of EVA is between 50% and 70%, which can provide sufficient support and comfort without excessively increasing the rigidity of the material, ensuring that the antibacterial and moisture-removing components are fully utilized in the material; within this time range, the heat is sufficiently transferred to each part of the composite material, so that the EVA and other components can fully react and form at a certain temperature; the temperature is controlled between 120 and 150°C, which can ensure that the EVA material melts and fully combines with the antibacterial and moisture-removing components; the molding time is between 10 and 30 minutes, which ensures that the components are fully mixed and solidified; The EVA material is a copolymer of ethylene and vinyl acetate, and the melt index is 10 to 50 g / 10 min; The melt index of EVA is 10-50g / 10min, which means that the material has moderate fluidity during heating, which can ensure sufficient mixing of the components and maintain stable molding performance during hot pressing. If the melt index is too low, the material may not have sufficient fluidity during heating, affecting the mixing effect; if the melt index is too high, it may cause the material to flow too quickly during molding, making it difficult to control the final shape; During the mixing process, all ingredients are fully mixed through the melt extrusion equipment to ensure that the composite material has a uniform distribution and no bubbles during the molding process; Through melt extrusion, the material can maintain fluidity when heated, so that the antibacterial and moisture-removing components can be evenly distributed in the EVA material. The temperature and pressure control of the extrusion process is very important. Too high temperature and pressure may cause degradation of the components, while too low temperature and pressure may cause uneven mixing.

[0013] Preferably, the moisture diffusion coefficient of the composite material is 10 -6 ~10 -4 m 2 / s, ensuring that moisture can be effectively discharged; the diffusion of moisture through the material is usually caused by molecular diffusion. Water vapor molecules gradually migrate to low concentration areas in the composite material through diffusion. A lower moisture diffusion coefficient (such as 10 -6 m 2 / s) means that moisture diffuses slowly, while a higher moisture diffusion coefficient (such as 10 -4 m 2 / s) means that moisture is discharged more quickly, which can improve the comfort inside the shoe; The moisture diffusion coefficient is determined by testing the water vapor transmission rate of the material, and the test method is ASTM E96 standard; ASTM E96 standard specifies the specific steps and test conditions for measuring water vapor transmission rate, ensuring the accuracy and comparability of the test results. The standard provides two test methods: sublimation method (cup method) and permeability method (dish method), which accurately calculate the moisture diffusion coefficient of the material by measuring the diffusion of water vapor under specific temperature and humidity conditions; During the test, the sample thickness of the composite material is 1.5 to 3 mm, and the test environment is 20 to 25° C. and 45 to 55% humidity; Composite materials with sample thickness of 1.5 to 3 mm can reflect their relatively high moisture permeability in the test and at the same time represent the effect in actual use. Under this temperature and humidity test environment (20 to 25°C, humidity 45 to 55%), the reliability and consistency of the test results can be guaranteed, making the test results of the moisture diffusion coefficient widely comparable.

[0014] Preferably, the antibacterial release rate of the composite material is not less than 2 mg / cm per hour. 2 , and remain stable within 100 hours; The antibacterial release rate of the material surface reflects its ability to release antibacterial components during use. A higher release rate can ensure that the growth of bacteria and fungi is effectively inhibited during use, thereby maintaining the antibacterial properties of the material. The release rate can directly affect the sustainability of the antibacterial effect. Therefore, it is necessary to ensure that the release rate is stable within 100 hours to meet the needs of long-term use; The antibacterial release rate is tested by the colloid method, the test solution is a simulated sweat solution, the temperature is controlled at 35-40°C, and the sample size is 2cm×2cm; Maintaining a stable antibacterial release rate within 100 hours means that the antibacterial components of the material will not be quickly depleted due to long-term contact with sweat or friction. Through reasonable antibacterial component loading and control of the material structure, excessive loss of antibacterial components can be effectively avoided, thereby ensuring the long-term effectiveness of antibacterial properties; The solution replacement cycle during the test is 24 hours, and the concentration of the released antibacterial components is measured each time to ensure the durability of the antibacterial effect; Replacing the test solution every 24 hours and measuring the concentration of antibacterial ingredients regularly can ensure the accuracy of the test results and the durability of the antibacterial effect. The temperature is controlled at 35-40°C, which is in line with the actual use environment of human skin.

[0015] The present invention also provides a method for applying the antibacterial and moisture-wicking composite material to sports shoes, comprising: Sole part: A composite material is used for the sole, which is foamed by EVA material with added graphene particles, combined with a silver ion composite and a copper-zinc alloy composite, and prepared by a hot pressing process to form a lightweight sole structure with excellent moisture conduction performance; Upper part: A composite material is used for the upper, the upper is made of a fabric blended with nano silver ion fiber and bamboo fiber, combined with a three-dimensional mesh microporous structure, and surface treated by impregnation with an antibacterial solution containing tea tree oil; Insole part: A composite material is used for the insole, which is composed of a multi-layer composite structure. The bottom layer is polyurethane foam to provide cushioning support; the middle layer is made of bamboo fiber sheets impregnated with tea tree oil solution; and the upper layer is coated with an antibacterial coating to form an insole with high moisture discharge efficiency.

[0016] The present invention provides an antibacterial moisture-wicking composite material, a preparation method and an application in sports shoes. It has the following beneficial effects: 1. The present invention adopts the foaming molding technology of graphene particles and EVA materials, so that the sole not only has a lightweight structure, but also has excellent moisture conductivity. Compared with the soles that simply rely on traditional materials in the prior art, the present invention greatly improves the moisture discharge efficiency, solves the odor problem caused by moisture accumulation, and improves the comfort and hygiene performance of wearing.

[0017] 2. The present invention enhances the antibacterial property and air permeability of the upper through the design of nano silver ion fiber and bamboo fiber blended fabric, combined with tea tree oil antibacterial solution treatment. Compared with traditional upper materials, the upper of the present invention can continuously resist bacterial growth, avoid bacterial growth and foot discomfort caused by long-term wear, and solve the problem of insufficient antibacterial property in the prior art.

[0018] 3. The insole of the present invention is designed with a multi-layer composite structure, which organically combines polyurethane foam, bamboo fiber and antibacterial coating, providing both cushioning support and efficient moisture removal. Different from the insoles of a single material in the prior art, the insole structure of the present invention can achieve better moisture discharge and antibacterial properties, significantly improving the dryness and comfort of the feet after long-term wear.

[0019] 4. The present invention adopts the synergistic antibacterial technology of silver ion composite and copper-zinc alloy composite to ensure that the composite material maintains a continuous antibacterial effect during long-term use, compared with the rapid failure of antibacterial materials in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Please refer to the attached Figure 1 : Embodiment 1: Preparation method of sports shoe sole Steps and process parameters: EVA material (ethylene-vinyl acetate copolymer) and graphene particles (5%) are mixed in proportion. The graphene particles are dispersed uniformly by ultrasonication in advance and mixed with the EVA material.

[0023] The mixed EVA and graphene materials are treated by a chemical foaming method, hydrated dichloromethane is selected as a foaming agent, and the added amount is controlled to be 3% of the total weight of the EVA.

[0024] The material is foamed and formed under the conditions of the foaming temperature being controlled at 70°C and the foaming time being 15 minutes. During the foaming process, the temperature change is maintained uniformly to ensure the stability of the foam expansion.

[0025] Addition of the silver ion complex and the copper-zinc alloy complex: add the prepared antibacterial complex into the sole foaming material at a ratio of 10% and stir evenly.

[0026] Through the hot pressing process, the molding temperature is set at 130°C and the molding time is 20 minutes to ensure that the antibacterial ingredients are evenly distributed in the sole.

[0027] The final result is a lightweight sole structure with excellent moisture conduction performance, which can effectively remove moisture and keep feet dry during exercise.

[0028] Embodiment 2: sports shoe upper preparation method Steps and process parameters: Nano silver ion fiber and bamboo fiber are blended in a ratio of 60:40 to make fabric.

[0029] The fabric is designed with a three-dimensional mesh microporous structure to make the fabric more breathable and comfortable.

[0030] Prepare a tea tree oil solution with a concentration of 7%. Soak the treated fabric in the solution for 30 minutes to ensure that the tea tree oil fully penetrates and forms an antibacterial layer.

[0031] The impregnated fabric is air-dried naturally to maintain the natural state of its fibers without affecting comfort.

[0032] Finally, the treated fabric is used in the upper part to ensure that the upper has excellent breathability and antibacterial properties.

[0033] Example 3: Preparation method of multi-layer composite structure of sports shoe insole Steps and process parameters: Polyurethane foam (PU foam) is used as the bottom material of the insole, a chemical foaming method is selected, the foaming temperature is set to 80° C., the foaming time is 15 minutes, and the added amount of the foaming agent is 4% of the total weight.

[0034] The bamboo fiber sheet is used as the middle layer of the insole. After being treated with acid and alkali to remove the natural resin, the bamboo fiber is soaked in a tea tree oil solution (concentration of 7%) for 2 hours.

[0035] By applying an antibacterial coating, a layer of antibacterial coating is applied to the upper layer of the insole to ensure that the antibacterial property is evenly distributed. The thickness of the coating is controlled at 0.5mm.

[0036] Each layer is formed by hot pressing, with the molding temperature set at 140°C and the molding time set at 20 minutes to ensure the stability of the multi-layer structure.

[0037] Example 4: Preparation and application of overall composite material for sports shoes Steps and process parameters: The EVA material is mixed with graphene particles, silver ion complex and copper-zinc alloy complex in a ratio of 70:10:10:10, and is fully mixed by melt extrusion equipment.

[0038] By chemical foaming method, a foaming agent (hydrated dichloromethane) was added, and the amount of the foaming agent added was 3% of the total weight. The foaming temperature was set at 75° C. and the foaming time was 15 minutes.

[0039] The foamed material was hot-pressed and the molding temperature was controlled at 120°C for 25 minutes.

[0040] The sole, upper, insole and other parts are assembled separately and fixed by hot pressing process to ensure the close connection between the parts.

[0041] Comparative Example 1: Comparative Experiment on Foaming Materials of Sports Shoes Soles Experimental Objective: To compare the moisture conductivity and antibacterial properties of the soles and evaluate the effect of mixing graphene particles with EVA materials.

[0042] Comparative Example Preparation Method: Material selection: The ratio of EVA material (ethylene-vinyl acetate copolymer) to graphene particles is adjusted to 0-3%, and the graphene particles are completely removed.

[0043] The same chemical foaming method as in Example 1 was used, with the addition amount of the foaming agent (hydrated dichloromethane) being 3% of the total weight of the EVA, the foaming temperature being set at 75° C., and the foaming time being 15 minutes.

[0044] The foamed mixed material is formed by hot pressing at a molding temperature of 120° C. and a molding time of 20 minutes.

[0045] Comparative Example 2: Comparison of antibacterial and breathable properties of upper materials Experimental objective: To test the antibacterial effect and breathability of the blended fabric of nano-silver ion fiber and bamboo fiber in the upper, and to compare the effects of different fiber combinations.

[0046] Comparative Example Preparation Method: Material selection: The ratio of bamboo fiber to nano silver ion fiber is adjusted from 60:40 in the embodiment to 80:20, thereby increasing the ratio of bamboo fiber.

[0047] Fabric treatment: Without adding tea tree oil solution, the bamboo fiber was pre-treated using only physical treatment (such as steam treatment) to remove surface impurities and grease.

[0048] Surface treatment: The tea tree oil impregnation step was omitted and a conventional antibacterial solution was used for surface treatment. The antibacterial solution had a lower concentration (5%) and did not contain tea tree oil.

[0049] Comparative Example 3: Comparison of moisture removal and antibacterial properties of multi-layer composite structures of insoles Experimental objectives: To test the moisture removal and antibacterial properties of insoles, and to evaluate the effects of different combinations of foams and bamboo fibers on performance.

[0050] Comparative Example Preparation Method: Bottom layer material: conventional polyurethane foam (PU foam) is used instead of the polyurethane foam in the embodiment, and bamboo fiber impregnated with tea tree oil is not added.

[0051] Middle layer: In the comparative example, the bamboo fiber sheet was not impregnated with the tea tree oil solution, and ordinary bamboo fiber sheets were used and directly spliced ​​on the middle layer of the polyurethane foam.

[0052] Coating treatment: The top layer is still coated with an antimicrobial coating, but does not contain tea tree oil. Standard antimicrobial coating materials are used, but at a lower concentration (1%).

[0053] Comparative Example 4: Preparation and application comparison of the overall composite material Experimental objectives: To compare the antibacterial properties, moisture discharge and comfort of the entire composite material, and to evaluate the effects of different component ratios on the overall performance.

[0054] Comparative Example Preparation Method: Material ratio: the ratio of the EVA material to the graphene particles, the silver ion complex and the copper-zinc alloy complex in the embodiment is adjusted from 70:10:10:10 to 80:10:5:5, and the ratio of the silver ion complex to the copper-zinc alloy complex is reduced.

[0055] Foaming and hot pressing process: Same as in the embodiment, chemical foaming and hot pressing molding process are used, but the addition of silver ions and copper-zinc alloy is reduced, resulting in a possible reduction in the antibacterial effect.

[0056] Antimicrobial coating: Use a regular antimicrobial coating instead of tea tree oil coating and reduce its concentration (only 1%).

[0057] Experiment 1: Comparative experiment on moisture conduction performance and comfort of the sole Experimental description: Purpose: To verify the effect of graphene particles on moisture emission and comfort of the soles by comparing the moisture conduction performance and comfort of the soles of Example 1 with those of Comparative Example 1.

[0058] Sample preparation: Example 1: EVA material and graphene particles (5%) were mixed in proportion. Hydrated dichloromethane was used as a foaming agent, and the amount of the foaming agent added was 3% of the total weight of EVA. The mixed material was foamed by a chemical foaming method at a foaming temperature of 75°C for 15 minutes, and then formed by a hot pressing process at 120°C for 20 minutes to obtain a sole sample.

[0059] Comparative Example 1: Graphene particles were removed, and the EVA material was mixed with a conventional foaming agent. The foaming process and hot pressing molding process were the same as in Example 1. The process parameters such as foaming temperature, foaming time, and molding temperature remained the same, and the only difference was that no graphene particles were added.

[0060] Test method: Moisture diffusion performance: Water vapor transmission rate (WVTR) test was performed using ASTM E96 standard. The sample thickness was set to 3mm, the test environment temperature was controlled at 35°C, and the humidity was maintained at 50%. The test solution was replaced every 24 hours, the amount of water vapor released was recorded, and the moisture diffusion coefficient was finally calculated.

[0061] Comfort test: Use a standard pressure tester to simulate the pressure (about 500N) applied by an athlete's foot to test the rebound performance and comfort of the sole. Record the rebound height and comfort score of the sole after being compressed.

[0062] Experimental setup: Five samples were prepared for each group of experiments. Each sample was tested for moisture emission and comfort respectively. The experimental period was 72 hours, and moisture vapor transmission rate and comfort tests were carried out every 24 hours.

[0063] Experimental data on the comparison of sole moisture conduction performance and comfort In Example 1, the addition of graphene particles significantly improves the moisture diffusion coefficient and comfort of the sole. Graphene not only improves the thermal conductivity of the material, but also enhances the moisture removal capacity of the sole. Through this design, the sole can more effectively take away sweat and quickly dissipate heat, thereby improving the comfort and overall experience of the wearer. In Comparative Example 1, after removing the graphene particles, the moisture discharge capacity is significantly reduced, the rebound performance of the sole after being compressed is also reduced, and the wearing experience is not as good as Example 1. This shows that the introduction of graphene particles plays a decisive role in moisture diffusivity and comfort.

[0064] The introduction of graphene particles enhances the resilience of the sole, because graphene helps optimize the microstructure of the material during the foaming process, making the sole rebound more quickly after being compressed, reducing the fatigue of the foot during exercise. Compared with Comparative Example 1, the resilience of the sole in Example 1 is better, indicating that the graphene particles not only affect the diffusion of moisture, but also have a positive effect on the mechanical properties of the sole.

[0065] From the experimental data, the moisture diffusion coefficient and comfort score of Example 1 are generally higher than those of Comparative Example 1, which proves the positive effect of the application of graphene in the sole material on improving the overall performance. This not only improves the wearing comfort, but also effectively solves the shortcomings of existing sole materials in terms of moisture management and comfort.

[0066] Experiment 2: Comparative experiment on antibacterial performance of shoe uppers Experimental description: Purpose: To compare the antibacterial and air permeability performance of the upper materials of Example 2 and Comparative Example 2, and to verify the effect of blending silver ion fiber with bamboo fiber and impregnation with tea tree oil on improving the antibacterial and air permeability of the upper.

[0067] Sample preparation: Embodiment 2: Nano silver ion fiber and bamboo fiber are blended in a ratio of 60:40 to make fabric. The fabric is designed with a three-dimensional mesh microporous structure to ensure high air permeability.

[0068] The blended fabric was soaked in a tea tree oil solution with a concentration of 7% for 30 minutes to ensure that the tea tree oil could fully penetrate and form an antibacterial layer on the surface. After treatment, the fabric was naturally air-dried.

[0069] Comparative Example 2: The proportion of bamboo fiber was adjusted to 80%, and no silver ion fiber was added. The fabric was also designed with a three-dimensional mesh microporous structure, but was not impregnated with tea tree oil. Instead, it was soaked in a conventional antibacterial solution (concentration of 5%) for 30 minutes and then naturally dried.

[0070] Test method: Antibacterial test: The antibacterial release rate was determined using the colloid method. Each sample (2 cm x 2 cm in size) was placed in a simulated sweat solution, the test temperature was controlled at 35°C, the solution was replaced every 24 hours and the concentration of the released antibacterial components was measured, and the test lasted for 100 hours.

[0071] Air permeability test: Use an air flow meter to test the air permeability of the upper fabric. Record the air flow through the fabric per unit time to measure the air permeability of the fabric.

[0072] Experimental setup: Five samples were prepared for each group of experiments, and antibacterial and air permeability tests were performed respectively. The experimental period was 100 hours, and samples were taken every 24 hours and the antibacterial data were recorded.

[0073] Comparative experimental data of antibacterial performance and breathability of shoe uppers From the experimental data, in Example 2, the combination of nano silver ion fiber and bamboo fiber blending and tea tree oil solution impregnation significantly improved the antibacterial and breathable properties of the upper. The antibacterial release rate in the example continued to maintain a high level, and the antibacterial component released per hour was not less than 2 mg / cm 2 , while in Comparative Example 2, since tea tree oil was not used for impregnation, the antibacterial effect was weak and the release rate was significantly lower than that of the embodiment. This shows that the composite design of silver ions and bamboo fibers not only improves the antibacterial properties of the upper, but also the impregnation of tea tree oil can effectively enhance the sustainability of the antibacterial effect.

[0074] From a mechanistic point of view, silver ion fiber forms a lasting antibacterial protective layer on the upper by continuously releasing silver ions, which can effectively inhibit the growth of bacteria. Unlike the bamboo fiber in Comparative Example 2, Example 2 breaks the problem of the decline of the antibacterial effect of traditional upper materials by adding nano silver ions, ensuring the stability of the antibacterial performance of the upper. Furthermore, the antibacterial and moisture-removing effects of tea tree oil, through its natural ingredients, not only inhibit bacteria, but also improve the moisture-removing properties of the upper, allowing sweat to evaporate quickly, thereby keeping the feet dry and avoiding the discomfort caused by moisture in traditional upper materials.

[0075] In addition, the design of the three-dimensional mesh microporous structure further improves the air permeability of the upper. The upper fabric of Example 2 optimizes air circulation through this structure, reduces the accumulation of heat, and makes the environment inside the shoe drier and more comfortable. This air permeability greatly improves the comfort when worn for a long time, and avoids the phenomenon of decreased air permeability after the proportion of bamboo fiber in the comparison group is increased. In general, the upper design of Example 2 not only provides a strong antibacterial effect, but also provides multiple guarantees in terms of air permeability and comfort.

[0076] Experiment 3: Comparative experiment on moisture dissipation and comfort of insoles Experimental description: Purpose: To compare the performance of Example 3 (multi-layer composite structure: polyurethane foam + bamboo fiber impregnated with tea tree oil) with that of Comparative Example 3 (conventional polyurethane foam, bamboo fiber not impregnated with tea tree oil) in terms of moisture discharge and comfort, and to verify the effect of the multi-layer composite structure on improving moisture discharge and comfort.

[0077] Sample preparation: Embodiment 3: The bottom layer uses polyurethane foam (PU foam), which is foamed by chemical foaming method, with a foaming temperature of 80°C, a foaming time of 15 minutes, and a foaming agent added in an amount of 4% of the total weight of the foam. After foaming, a foam layer with good elasticity and cushioning performance is obtained.

[0078] The middle layer uses bamboo fiber sheets, which are impregnated with tea tree oil solution at a concentration of 7% for 2 hours. The bamboo fiber absorbs the antibacterial components of tea tree oil, enhancing its antibacterial and moisture-wicking properties.

[0079] The upper layer is coated with an antibacterial coating with a coating concentration of 1% to ensure the durability of the antibacterial effect.

[0080] Comparative Example 3: The bottom layer also uses polyurethane foam, and the foaming process is the same as in the embodiment, but no tea tree oil is added to impregnate bamboo fiber, and the middle layer is a conventional bamboo fiber sheet without antibacterial impregnation. The upper layer is still coated with a common antibacterial coating with a concentration of 1%.

[0081] Test method: Moisture dissipation test: Use ASTM E96 standard to test the water vapor permeability of the sample. Set the thickness of the insole sample to 5mm, the test environment temperature to 35℃, and the humidity to 50%. Replace the test solution every 24 hours and measure the amount of water vapor released to calculate the moisture diffusion coefficient.

[0082] Comfort test: Use a pressure tester to simulate the pressure (about 500N) applied by an athlete's foot to test the rebound performance of the insole. Record the rebound height and comfort score of the insole after being compressed.

[0083] Experimental setup: Five samples were prepared for each group of experiments, and moisture emission and comfort tests were conducted respectively. The experimental period was 72 hours, and moisture vapor transmission rate and comfort tests were conducted every 24 hours.

[0084] Comparative experimental data of moisture dissipation and comfort of insoles In the experimental data, Example 3 is significantly better than Comparative Example 3, and performs more prominently in terms of moisture emission and comfort. The moisture diffusion coefficient of Example 3 is generally higher than that of Comparative Example 3, and the comfort rebound height is also much higher than that of Comparative Example 3. The experimental results show that tea tree oil-impregnated bamboo fiber significantly enhances the moisture emission of the insole, and improves its long-lasting antibacterial effect through the antibacterial coating. The moisture diffusion of Comparative Example 3 is poor, indicating that the bamboo fiber without tea tree oil impregnation is far inferior to Example 3 in terms of moisture emission.

[0085] From a mechanism analysis, the natural hygroscopicity of bamboo fiber and the dehumidification effect of tea tree oil work together to enable the insole of Example 3 to quickly absorb and discharge moisture from the foot. The volatility of tea tree oil and its natural antibacterial components enhance the bamboo fiber, providing a better moisture evaporation effect and keeping the insole dry and clean at all times. In contrast, although the bamboo fiber in Comparative Example 3 has a certain hygroscopicity, it lacks the auxiliary effect of tea tree oil, resulting in the inability to quickly discharge moisture, and poor comfort and dehumidification effects.

[0086] In addition, the polyurethane foam layer in Example 3 provides effective cushioning support, and the tea tree oil impregnated in the bamboo fiber not only inhibits the growth of bacteria, but also further promotes the moisture discharge of the insole. Although Comparative Example 3 uses a conventional antibacterial coating, due to the lack of tea tree oil and the unique volatility of tea tree oil, the moisture discharge and antibacterial effect are not as good as those of Example 3.

[0087] Example 3 effectively improves the moisture discharge capacity and comfort of the insole by reasonably combining the multi-layer composite structure with the tea tree oil-impregnated bamboo fiber, and solves the problem of moisture accumulation in traditional insoles after long-term use.

[0088] Experiment 4: Comprehensive performance comparison experiment of integral composite materials Experimental description: Purpose: To compare the performance of Example 4 (overall composite material: EVA+graphene+silver ion composite) with that of Comparative Example 4 (EVA+graphene+reduced antibacterial component) in terms of antibacterial property, moisture emission and comfort, and to verify the advantages of the present invention in comprehensive performance.

[0089] Sample preparation: Embodiment 4: The EVA material was mixed with 5% graphene particles, silver ion complex and copper-zinc alloy complex in a ratio of 70:10:10:10 and treated by chemical foaming. The amount of foaming agent (hydrated dichloromethane) added was 3% of the total weight, the foaming temperature was set at 75°C, and the foaming time was 15 minutes. Then, a composite material of the upper, sole and insole was obtained by hot pressing molding process at a molding temperature of 120°C and a molding time of 25 minutes.

[0090] Comparative Example 4: The ratio of the silver ion complex and the copper-zinc alloy complex was reduced to 5%, and the tea tree oil was removed. Other materials and process parameters were the same as those in the embodiment.

[0091] Test method: Antibacterial test: The antibacterial release rate was tested using the colloid method. Each sample (size 2cm×2cm) was immersed in a simulated sweat solution, the temperature was controlled at 35°C, the solution was replaced every 24 hours, the test lasted for 100 hours, and the release concentration of the antibacterial components was recorded.

[0092] Moisture emission: The water vapor transmission rate was tested using the ASTM E96 standard. The thickness of the sole was 3 mm. The test environment temperature was set at 35°C and the humidity was 50%. The solution was replaced every 24 hours and the moisture diffusion coefficient was recorded.

[0093] Comfort test: Use a pressure tester to simulate foot pressure (about 500N) to test the resilience, comfort and pressure distribution of the sole. Record the rebound height and comfort score of the sole after pressure.

[0094] Experimental setup: Five samples were prepared for each group of experiments, and antibacterial, moisture emission and comfort tests were conducted respectively. The experimental period was 100 hours, and samples were collected every 24 hours and relevant data were recorded.

[0095] Experimental data on the comprehensive performance comparison of the overall composite material The experimental results clearly show that the composite material of Example 4 is significantly better than that of Comparative Example 4 in terms of moisture emission, comfort and antibacterial properties. The moisture diffusion coefficient in Example 4 is significantly higher than that in Comparative Example 4, indicating that after adding graphene particles and high-concentration antibacterial components (silver ions and copper-zinc alloy composites), the composite material has stronger moisture emission capacity and higher comfort. In contrast, Comparative Example 4, which removes part of the antibacterial components and reduces the amount of tea tree oil used, has weaker moisture emission capacity and comfort.

[0096] From a mechanism point of view, the addition of graphene particles not only provides a higher moisture conductivity of the material, but also promotes the diffusion of moisture molecules through its high specific surface area, accelerates the evaporation of sweat and water vapor, avoids moisture retention in the shoe, and keeps the feet dry. In addition, the antibacterial effect of the silver ion and copper-zinc alloy composite can be continuously released in Example 4, thereby preventing the growth of bacteria and the generation of odor. In comparison, in Comparative Example 4, due to the reduced concentration of antibacterial components, the antibacterial effect is poor, and moisture emission and comfort are limited.

[0097] The addition of tea tree oil not only enhances the antibacterial property in Example 4, but also promotes the moisture discharge in the shoe through its natural volatility, so that the insole can be kept dry continuously. In Comparative Example 4, the moisture discharge effect is significantly reduced due to the lack of the assistance of tea tree oil and high concentration of antibacterial ingredients, resulting in relatively poor comfort and antibacterial effect of the insole.

[0098] Example 4 not only improves the moisture discharge of the insole, but also ensures its antibacterial properties and comfort by reasonably combining high-concentration antibacterial ingredients and graphene particles, thereby solving the problems of antibacterial effect decay and moisture retention in the prior art.

[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An antibacterial and moisture-wicking composite material, characterized in that: The composite material comprises the following components in parts by weight: Silver ion complex: 50-70 parts; Copper-zinc alloy composite: 30-50 parts; Graphene: 3-6 parts; Bamboo fiber: 10-20 parts; Polyurethane foam: 5-10 parts; EVA material: 50-70 parts; Tea tree oil: 0.5-2 parts.

2. A method for preparing an antibacterial and moisture-wicking composite material, characterized in that: Using the antibacterial moisture-wicking composite material according to claim 1, the method comprises the following steps: S1, preparing an antibacterial component, mixing a silver ion solution and a copper-zinc alloy powder in proportion, reacting at a temperature of 100 to 150° C. for 2 to 4 hours to form a composite of silver ions and the copper-zinc alloy; S2, preparing a dehumidification component, mixing the graphene powder with a solvent by ultrasonic dispersion to ensure uniform distribution of the graphene; S3, preparing bamboo fiber, first pre-treating to remove impurities, then soaking the bamboo fiber in a tea tree oil solution with a soaking concentration of 5-10%, and drying the soaked bamboo fiber; S4, preparing polyurethane foam by chemical foaming method, the foaming temperature is controlled at 60-80° C., the foaming time is 10-20 minutes, and the amount of foaming agent added is 2-5% of the total weight of the polyurethane foam; S5. Mix the antibacterial component, the moisture-removing component and the EVA material, and obtain an antibacterial and moisture-removing composite material by a hot pressing molding method with the temperature controlled between 120 and 150° C. and the molding time being 10 to 30 minutes.

3. The method for preparing an antibacterial and moisture-wicking composite material according to claim 2, characterized in that: The preparation method of the silver ion complex and the copper-zinc alloy complex is as follows: The silver ion solution and the copper-zinc alloy powder are mixed in a weight ratio of 50 to 80 parts of silver ions to 20 to 50 parts of copper-zinc alloy, the reaction temperature is controlled between 100 and 150° C., and the reaction time is 2 to 4 hours; The silver ion solution is a water-soluble silver salt solution, and the particle size of the copper-zinc alloy powder ranges from 1 to 5 microns; The mixing reaction is carried out under a constant temperature condition, and an appropriate amount of reducing agent can be added during the mixing process to promote the composite reaction of silver ions and copper-zinc alloy.

4. The method for preparing an antibacterial and moisture-wicking composite material according to claim 2, characterized in that: The graphene dispersion method comprises: Mixing graphene powder with solvent and evenly dispersing it through an ultrasonic dispersing device to ensure uniform distribution of graphene and avoid agglomeration; The solvent is water, ethanol or ethylene glycol, the power of the ultrasonic dispersion device is 200 to 500 W, and the ultrasonic treatment time is 30 to 60 minutes; During the dispersion process, a dispersant is added to ensure that the graphene is stably dispersed and not easily aggregated.

5. The method for preparing an antibacterial and moisture-wicking composite material according to claim 2, characterized in that: The pretreatment step of the bamboo fiber comprises: After the bamboo fiber is physically treated to remove surface impurities, it is then chemically treated to remove oil and natural resin. After the treatment, tiny pores are formed on the surface of the bamboo fiber, which improves its ability to bind to tea tree oil. Physical treatment methods include steam treatment or mechanical stretching, and chemical treatment includes acid and alkali treatment; The soaking concentration in the tea tree oil solution is 5-10%, and the soaking time is 2-4 hours. After that, the bamboo fiber is naturally air-dried or dried to remove excess solvent and maintain the natural properties of the bamboo fiber.

6. The method for preparing an antibacterial and moisture-wicking composite material according to claim 2, characterized in that: The foaming process of the polyurethane foam comprises: The foam is prepared by chemical foaming method, the foaming temperature is controlled between 60 and 80°C, the foaming time is 10 to 20 minutes, and the amount of foaming agent added is 2 to 5% of the total weight of the polyurethane foam; The chemical foaming agent is hydrated dichloromethane or an alkyl sulfonate compound, and the volume expansion coefficient of the foam is 3 to 5 times; During the foaming process, the foaming agent and the polyurethane are evenly mixed and then heated for reaction. The temperature change during the foaming process is controlled between 70 and 85° C. to ensure that the foam structure is uniform and stable.

7. The method for preparing an antibacterial and moisture-wicking composite material according to claim 2, characterized in that: The mixing method of the EVA material comprises: The antibacterial component, the moisture removal component and the EVA material are mixed in a ratio of 50 to 70 parts, and hot-pressed to form the mixture. The forming temperature is controlled between 120 and 150° C., and the forming time is 10 to 30 minutes. The EVA material is a copolymer of ethylene and vinyl acetate, and the melt index is 10 to 50 g / 10 min; During the mixing process, all ingredients are thoroughly mixed through the melt extrusion equipment to ensure that the composite material has a uniform distribution and no bubbles during the molding process.

8. The method for preparing an antibacterial and moisture-wicking composite material according to claim 2, characterized in that: The moisture diffusion coefficient of the composite material is 10 -6 ~10 -4 m 2 / s, ensuring moisture can be effectively discharged; The moisture diffusion coefficient is determined by testing the water vapor transmission rate of the material, and the test method is ASTM E96 standard; During the test, the sample thickness of the composite material is 1.5-3 mm, and the test environment is at a temperature of 20-25° C. and a humidity of 45-55%.

9. The method for preparing an antibacterial and moisture-wicking composite material according to claim 2, characterized in that: The antibacterial release rate of the composite material is not less than 2 mg / cm per hour. 2 , and remain stable within 100 hours; The antibacterial release rate is tested by the colloid method, the test solution is a simulated sweat solution, the temperature is controlled at 35-40°C, and the sample size is 2cm×2cm; The solution replacement cycle during the test is 24 hours, and the concentration of the released antibacterial components is measured each time to ensure the durability of the antibacterial effect.

10. A method for applying an antibacterial and moisture-wicking composite material to sports shoes, characterized in that: The antibacterial and moisture-wicking composite material according to claim 1 comprises: Sole part: A composite material is used for the sole, which is foamed by EVA material with added graphene particles, combined with a silver ion composite and a copper-zinc alloy composite, and prepared by a hot pressing process to form a lightweight sole structure with excellent moisture conduction performance; Upper part: A composite material is used for the upper, the upper is made of a fabric blended with nano silver ion fiber and bamboo fiber, combined with a three-dimensional mesh microporous structure, and surface treated by impregnation with an antibacterial solution containing tea tree oil; Insole part: A composite material is used for the insole, which is composed of a multi-layer composite structure. The bottom layer is polyurethane foam to provide cushioning support; the middle layer is made of bamboo fiber sheets impregnated with tea tree oil solution; and the upper layer is coated with an antibacterial coating to form an insole with high moisture discharge efficiency.